A method for preparing a five-layer co-extruded polyethylene film and its application in silo bags

By adding nano-hollow microspheres and inclusion cyclodextrin in the preparation process of the polyethylene film for silo bags, and using bidirectional synchronous stretching technology, the problems of uneven film thickness and uneven performance distribution are solved, and a high-performance and high-strength five-layer co-extruded polyethylene film is achieved.

CN118952605BActive Publication Date: 2025-03-28SHANDONG LONGXING PLASTIC FILM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411433245.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-28
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The thickness of the existing polyethylene films for silo bags is uneven, resulting in uneven distribution of barrier properties, puncture resistance, tensile strength and impact strength, and is easy to delaminate during preparation and long-term use.

Method used

The preparation method of five-layer coextruded polyethylene film is adopted. By adding nano-hollow microspheres and inclusion cyclodextrin to the polyethylene layer, barrier layer and bonding layer, the fluidity and adhesion of the raw materials are improved, and the uniformity and strength of the film are ensured through bidirectional synchronous stretching technology.

Benefits of technology

The thickness and performance distribution of five-layer coextruded polyethylene film are achieved, and barrier properties, puncture resistance, tensile strength and impact strength are improved, and they are not easy to delaminate during preparation and long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a five-layer co-extruded polyethylene film and application thereof in a silo bag, belonging to the technical field of plastic films. The preparation method comprises the following steps: preparing a mixed polyethylene material, preparing a binder, preparing a barrier material, and melt co-extruding; in preparing the mixed polyethylene material, metallocene polyethylene resin, high-density polyethylene resin, and nano hollow microspheres are uniformly mixed to obtain a mixed polyethylene material; in preparing the binder, low-density polyethylene resin and inclusion cyclodextrin are uniformly mixed to obtain a binder; the five-layer co-extruded polyethylene film prepared by the invention has good barrier property and puncture resistance, high tensile strength and impact strength, uniform thickness, uniform distribution of barrier property, puncture resistance, tensile strength, and impact strength, and is not easy to be delaminated during preparation and long-term use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic films, and in particular to a preparation method of a five-layer co-extruded polyethylene film and application of the film in a silo bag. Background Art

[0002] Silos are divided into two categories: agricultural silos and industrial silos. Among them, agricultural silos are closed grain storage facilities that can store various agricultural products. They have excellent fresh-keeping, insect-proof and moisture-proof properties, but they have high investment costs and occupy a large area. Silo bags are a portable grain storage system that can overcome the shortcomings of silos. They not only have excellent barrier properties, puncture resistance, tensile strength, and impact strength, but also have low costs and can achieve on-site storage. Therefore, with the vigorous development of agriculture, the demand for silo bags is also increasing.

[0003] The material of existing silo bags is mainly polyethylene resin. During the preparation, polyethylene resin is first used as the raw material to form a film to obtain a polyethylene film for silo bags, and then the bag is made to obtain a silo bag. When making the film, multi-layer co-extrusion technology is generally used. Multi-layer co-extrusion technology refers to the technology of simultaneously extruding and layering two or more different melts into a film through multiple extrusion ports of the same die of the same extruder. The multi-layer co-extrusion technology utilizes multi-layer composite molding to prepare a composite film of a combination of multiple materials in a single extrusion process, and to achieve a firm bond between the layers of materials, thereby combining the excellent properties of multiple materials. Therefore, when making the film, the multi-layer co-extrusion technology is used to allow multiple materials to enter the same die in layers at the same time and extrude and compound them at a certain level, so that a polyethylene film with excellent barrier properties, puncture resistance, tensile strength, and impact strength can be obtained.

[0004] For polyethylene film for silo bags, five-layer co-extrusion technology is mainly used. From top to bottom, they are polyethylene layer, adhesive layer, barrier layer, adhesive layer, and polyethylene layer. Among them, the material used for the polyethylene layer is generally metallocene polyethylene, the material used for the adhesive layer is generally low-density polyethylene, and the material used for the barrier layer is generally ethylene-vinyl alcohol copolymer. After extrusion and compounding, biaxial stretching technology is mainly used to prepare polyethylene film for silo bags with high orientation.

[0005] However, when the above method is used to prepare polyethylene film for silo bags, the following problems exist: the poor fluidity of metallocene polyethylene and ethylene-vinyl alcohol copolymer leads to uneven thickness of the prepared polyethylene film for silo bags, which further leads to uneven distribution of barrier properties, puncture resistance, tensile strength and impact strength of the prepared polyethylene film for silo bags; the poor adhesion of low-density polyethylene leads to easy delamination of the prepared polyethylene film for silo bags during preparation and long-term use.

[0006] In order to solve the above problems, the most commonly used method at present is to add surface modified fillers to the materials used for the polyethylene layer and the barrier layer, and to add ethylene copolymers to the materials used for the bonding layer, wherein the surface modified fillers are specifically fillers that have been surface-modified by surfactants or silane coupling agents, and the addition of surface modified fillers can improve the fluidity of metallocene polyethylene and ethylene-vinyl alcohol copolymers; ethylene copolymers are specifically copolymers of ethylene and other monomers, and the addition of ethylene copolymers can improve the adhesion of low-density polyethylene.

[0007] However, since the commonly used surface modified fillers are generally porous structures, they will affect the barrier properties of the polyethylene layer and the barrier layer, further affecting the barrier properties of the prepared polyethylene film for silo bags; the addition of ethylene copolymers will affect the crystallinity of the low-density polyethylene in the adhesive layer, resulting in a decrease in the strength and barrier properties of the adhesive layer, further affecting the barrier properties, puncture resistance, tensile strength and impact strength of the prepared polyethylene film for silo bags. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a method for preparing a five-layer co-extruded polyethylene film and application of the film in a silo bag. The prepared five-layer co-extruded polyethylene film has good barrier properties and puncture resistance, high tensile strength and impact strength, uniform thickness, and uniform distribution of barrier properties, puncture resistance, tensile strength and impact strength, and is not easy to delaminate during preparation and long-term use.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing a five-layer co-extruded polyethylene film, comprising the following steps: preparing a mixed polyethylene material, preparing a bonding material, preparing a barrier material, and melt co-extruding;

[0011] The mixed polyethylene material is prepared by uniformly mixing metallocene polyethylene resin, high-density polyethylene resin and nano hollow microspheres to obtain a mixed polyethylene material;

[0012] In the preparation of the mixed polyethylene material, the mass ratio of the metallocene polyethylene resin, the high-density polyethylene resin, and the nano hollow microspheres is 85-90:15-18:6-7;

[0013] The density of the metallocene polyethylene resin is 0.918 g / cm 3 , the melt index at 190°C and 2.16kg is 1.0g / 10min;

[0014] The density of the high-density polyethylene resin is 0.961 g / cm 3 , the melt index at 190°C and 2.16kg is 0.7g / 10min;

[0015] The preparation method of the hollow nanospheres comprises the following steps: surface modification, cross-linking modification, acidification, and alkalization;

[0016] The surface modification comprises mixing nano calcium carbonate, vinyl trimethoxysilane and anhydrous ethanol, stirring at a stirring speed of 100-200 rpm for 30-40 min at room temperature, dropping ammonia water to adjust the pH to 8-9, continuing stirring for 5-6 h, centrifuging at a centrifugal speed of 10000-11000 rpm for 15-16 min, taking a precipitate, washing the precipitate with anhydrous ethanol and drying it to obtain a surface-modified nano calcium carbonate;

[0017] In the surface modification, the mass ratio of nano calcium carbonate, vinyl trimethoxy silane and anhydrous ethanol is 90-100:500-600:7500-8500;

[0018] The particle size of the nano calcium carbonate is 100 nm;

[0019] The mass content of the ammonia water is 25%, and the dropping speed is 5-6g / min;

[0020] The cross-linking modification comprises mixing the surface-modified nano-calcium carbonate, methacrylic acid, divinylbenzene and acetonitrile, stirring and refluxing at 90-100° C. for 10-20 minutes, adding azobisisobutyronitrile, continuing to stir and reflux for 2-2.5 hours, centrifuging at a centrifugal speed of 10000-11000 rpm for 15-16 minutes, taking a precipitate, washing the precipitate with acetonitrile and drying the precipitate to obtain a cross-linked modified nano-calcium carbonate;

[0021] In the cross-linking modification, the mass ratio of surface-modified nano-calcium carbonate, methacrylic acid, divinylbenzene, acetonitrile, and azobisisobutyronitrile is 100-110:300-360:210-260:30000-35000:4-6;

[0022] The acidification comprises mixing the cross-linked modified nano-calcium carbonate and the hydrochloric acid aqueous solution, stirring at a stirring speed of 300-400 rpm for 15-20 min at room temperature, centrifuging at a centrifugal speed of 17000-18000 rpm for 24-26 min, taking the precipitate, washing the precipitate with deionized water and drying it to obtain the acidified microspheres;

[0023] In the acidification, the mass ratio of the cross-linked modified nano-calcium carbonate to the hydrochloric acid aqueous solution is 110-120:4200-4500;

[0024] The mass content of the hydrochloric acid aqueous solution is 10%;

[0025] The alkalization comprises mixing the acidified microspheres and the sodium hydroxide aqueous solution, stirring at a stirring speed of 300-400 rpm for 15-20 min at room temperature, centrifuging at a centrifugal speed of 17000-18000 rpm for 24-26 min, taking the precipitate, washing the precipitate with deionized water and drying it to obtain the nano hollow microspheres;

[0026] In the alkalization, the mass ratio of the acidified microspheres to the sodium hydroxide aqueous solution is 80-90:4000-4500;

[0027] The mass content of the sodium hydroxide aqueous solution is 10%;

[0028] In the preparation of the binder, low-density polyethylene resin and inclusion cyclodextrin are uniformly mixed to obtain the binder;

[0029] In the preparation of the binder, the mass ratio of the low-density polyethylene resin to the inclusion cyclodextrin is 85-90:8-10;

[0030] The density of the low-density polyethylene resin is 0.924 g / cm 3 , the melt index at 190°C and 2.16kg is 4.0g / 10min;

[0031] The preparation method of the inclusion cyclodextrin is as follows: after mixing β-cyclodextrin and deionized water, stirring at a stirring speed of 300-400 rpm at 40-50° C. for 20-30 minutes, adding polycaprolactone-polyethylene glycol block copolymer, continuing stirring for 20-30 minutes, naturally cooling to room temperature, ultrasonically shaking, standing for 10-12 hours, adding polyvinyl alcohol, stirring at a stirring speed of 300-400 rpm at 40-50° C. for 40-50 minutes, naturally cooling to room temperature, continuing stirring for 40-50 minutes, standing for 10-12 hours, spray drying, controlling the inlet air temperature to be 130-140° C., and the outlet air temperature to be 60-70° C., to obtain the inclusion cyclodextrin;

[0032] In the preparation of the inclusion cyclodextrin, the mass ratio of β-cyclodextrin, deionized water, polycaprolactone-polyethylene glycol block copolymer, and polyvinyl alcohol is 50-55:3700-4000:10-12:14-16;

[0033] The weight average molecular weight of the polycaprolactone-polyethylene glycol block copolymer is 2000, wherein the weight average molecular weight of the caprolactone segment is 1000 and the weight average molecular weight of the ethylene glycol segment is 1000;

[0034] The weight average molecular weight of the polyvinyl alcohol is 10,000, and the alcoholysis degree is 98%;

[0035] The frequency of the ultrasonic oscillation is 20-25kHz, and the duration is 15-20min;

[0036] The barrier material is prepared by uniformly mixing dried ethylene-vinyl alcohol copolymer, high-density polyethylene resin and nano hollow microspheres to obtain the barrier material;

[0037] In the preparation of the barrier material, the mass ratio of the dried ethylene-vinyl alcohol copolymer, the high-density polyethylene resin, and the nano hollow microspheres is 80-85:20-23:7-8;

[0038] The preparation method of the dried ethylene-vinyl alcohol copolymer is as follows: drying the ethylene-vinyl alcohol copolymer at 120-125° C. to a moisture content of 0.01-0.04% to obtain a dried ethylene-vinyl alcohol copolymer;

[0039] The molar content of vinyl in the ethylene-vinyl alcohol copolymer is 32%, and the melt index at 210° C. and 2.16 kg is 1.6 g / 10 min;

[0040] The density of the high-density polyethylene resin is 0.961 g / cm 3 , the melt index at 190°C and 2.16kg is 0.7g / 10min;

[0041] The preparation method of the nano hollow microspheres is the same as the preparation method of the nano hollow microspheres in the polyethylene layer raw material;

[0042] In the melt coextrusion, the raw material mixed polyethylene material of polyethylene layer I, the raw material adhesive material of bonding layer I, the raw material barrier material of barrier layer, the raw material adhesive material of bonding layer II, and the raw material mixed polyethylene material of polyethylene layer II are respectively put into five hoppers of the extruder, and melted respectively to obtain melts, and the melts are respectively made to enter different extrusion ports, and extruded in the order of polyethylene layer I, bonding layer I, barrier layer, bonding layer II, and polyethylene layer II, and then introduced into the same die head for composite molding, and then cooled to obtain a cast sheet, and the cast sheet is preheated, bidirectional synchronous stretching is performed, and then shaping is performed to obtain a five-layer co-extruded polyethylene film;

[0043] In the melt coextrusion, the mass ratio of the raw material mixed polyethylene material of the polyethylene layer I, the raw material adhesive material of the bonding layer I, the raw material barrier material of the barrier layer, the raw material adhesive material of the bonding layer II, and the raw material mixed polyethylene material of the polyethylene layer II is 27-30:16-18:17-20:16-18:27-30;

[0044] The melting temperature of the mixed polyethylene material is 190-200°C;

[0045] The melting temperature of the adhesive is 185-195°C;

[0046] The melting temperature of the barrier material is 200-210°C;

[0047] The cooling temperature is 20-25°C;

[0048] The preheating temperature is 130-140°C;

[0049] The temperature of the bidirectional synchronous stretching is 125-135°C, the transverse stretching ratio is 5-6:1, and the longitudinal stretching ratio is 5-6:1;

[0050] The setting temperature is 125-140°C.

[0051] Application of the five-layer co-extruded polyethylene film obtained by the above-mentioned preparation method in silo bags.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The preparation method of the five-layer co-extruded polyethylene film of the present invention comprises adding hollow nanospheres to the raw materials of the polyethylene layer I, the barrier layer and the polyethylene layer II. The preparation method of the hollow nanospheres comprises surface modification, crosslinking modification, acidification and alkalization. The surface modification comprises using vinyl trimethoxysilane to modify the surface of nano calcium carbonate, introducing carbon-carbon double bonds on the surface of the nano calcium carbonate to obtain surface modified nano calcium carbonate. The crosslinking modification comprises using methyl methacrylate as a comonomer and divinyl benzene as a crosslinking agent to crosslink the carbon-carbon double bonds on the surface of the surface modified nano calcium carbonate, thereby introducing a crosslinking layer on the surface of the nano calcium carbonate to obtain crosslinked modified nano calcium carbonate. The acidification comprises using hydrochloric acid aqueous solution to acidify the crosslinked modified nano calcium carbonate. The method comprises the following steps: alkalizing the acidified microspheres with an aqueous sodium hydroxide solution to remove calcium carbonate, thereby obtaining acidified microspheres; alkalizing the acidified microspheres with an aqueous sodium hydroxide solution, thereby reacting with carboxylic acid in the acidified microspheres to generate sodium carboxylate groups, thereby obtaining nano hollow microspheres with sodium carboxylate groups. After the nano hollow microspheres are added to the raw materials of the polyethylene layer I, the barrier layer, and the polyethylene layer II, the fluidity of the raw materials can be improved, thereby ensuring that the thickness of the prepared five-layer co-extruded polyethylene film is uniform, and the barrier properties, puncture resistance, tensile strength, and impact strength are uniformly distributed; and the sodium carboxylate group can also act as a nucleating agent, thereby increasing the crystallization rate of polyethylene in the polyethylene layer I, the barrier layer, and the polyethylene layer II, thereby increasing the barrier properties of the prepared five-layer co-extruded polyethylene film. energy, puncture resistance, tensile strength, and impact strength; in addition, inclusion cyclodextrin is added to the raw materials of the adhesive layer I and the adhesive layer II. The preparation method of the inclusion cyclodextrin is as follows: after β-cyclodextrin is mixed with the polycaprolactone-polyethylene glycol block copolymer, the hydrophobic inner cavity of the β-cyclodextrin is combined with the caprolactone segment of the polycaprolactone-polyethylene glycol block copolymer, thereby encapsulating the polycaprolactone-polyethylene glycol block copolymer, and the hydrophilic outer surface of the β-cyclodextrin is combined with the ethylene glycol segment of the polycaprolactone-polyethylene glycol block copolymer, and then polyvinyl alcohol is added, and the polyvinyl alcohol is combined with the ethylene glycol segment of the polycaprolactone-polyethylene glycol block copolymer in the hydrophobic inner cavity, thereby obtaining a hydrophobic outer layer, and the inner cavity sequentially includes the polycaprolactone-polyethylene glycol block copolymer. , polyvinyl alcohol-enclosed cyclodextrin, after the enclosed cyclodextrin is added to the raw materials of the adhesive layer I and the adhesive layer II, the hydrophobic group of the outer layer ensures the compatibility of the enclosed cyclodextrin with the low-density polyethylene resin, and can also avoid the influence of the direct addition of polyvinyl alcohol on the fluidity of the low-density polyethylene resin. During preheating and biaxial synchronous stretching, the polyvinyl alcohol in the enclosed cyclodextrin and the polycaprolactone-polyethylene glycol block copolymer are released at high temperature, and the polyvinyl alcohol further plays a bonding role, thereby improving the peel strength of the prepared five-layer co-extruded polyethylene film, ensuring that it is not easy to delaminate during preparation and long-term use; the addition of cyclodextrin can also improve the barrier properties, puncture resistance, tensile strength, and impact strength of the prepared five-layer co-extruded polyethylene film;

[0054] (2) The method for preparing a five-layer co-extruded polyethylene film of the present invention has good barrier properties and a water vapor permeability of 1.4-1.7 g / (m 2 ·day), oxygen permeability is 1.7-2.1cm 3 / (m 2 ·day·bar);

[0055] (3) The method for preparing a five-layer co-extruded polyethylene film of the present invention has good puncture resistance and a puncture strength of 19.2-19.6N;

[0056] (4) The method for preparing a five-layer co-extruded polyethylene film of the present invention has high tensile strength, with a transverse tensile strength of 90.3-94.7 MPa and a longitudinal tensile strength of 79.4-81.1 MPa;

[0057] (5) The method for preparing a five-layer co-extruded polyethylene film of the present invention has high impact strength, and the drop impact strength (A method) is 687-711g;

[0058] (6) The method for preparing a five-layer co-extruded polyethylene film of the present invention has a uniform thickness, and the barrier properties, puncture resistance, tensile strength, and impact strength of the prepared five-layer co-extruded polyethylene film are uniformly distributed;

[0059] (7) The method for preparing a five-layer co-extruded polyethylene film of the present invention has a high peel strength of 8.7-9.0 N / 15 mm, thereby ensuring that the film is not easily delaminated during preparation and long-term use. DETAILED DESCRIPTION

[0060] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0061] Example 1

[0062] A method for preparing a five-layer co-extruded polyethylene film, specifically comprising:

[0063] 1. Preparation of mixed polyethylene material: metallocene polyethylene resin, high-density polyethylene resin and nano hollow microspheres are uniformly mixed in a mass ratio of 85:15:6 to obtain a mixed polyethylene material;

[0064] The density of the metallocene polyethylene resin is 0.918 g / cm 3 , the melt index at 190°C and 2.16kg is 1.0g / 10min;

[0065] The density of the high-density polyethylene resin is 0.961 g / cm3 , the melt index at 190°C and 2.16kg is 0.7g / 10min;

[0066] The preparation method of the hollow nanospheres is as follows:

[0067] (1) Surface modification: 90 g of nano-calcium carbonate, 500 g of vinyltrimethoxysilane and 7500 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 100 rpm for 30 min, ammonia water was added dropwise to adjust the pH to 8, stirring was continued for 5 h, centrifuged at a centrifugal speed of 10000 rpm for 15 min, the precipitate was taken, the precipitate was washed with anhydrous ethanol and then dried to obtain surface-modified nano-calcium carbonate;

[0068] The particle size of the nano calcium carbonate is 100 nm;

[0069] The mass content of the ammonia water is 25%, and the dropping speed is 5-6g / min;

[0070] (2) Cross-linking modification: 100 g of surface-modified nano-calcium carbonate, 300 g of methacrylic acid, 210 g of divinylbenzene and 30,000 g of acetonitrile were mixed, stirred and refluxed at 90° C. for 10 min, 4 g of azobisisobutyronitrile was added, and the mixture was stirred and refluxed for 2 h. The mixture was centrifuged at 10,000 rpm for 15 min, and the precipitate was taken. The precipitate was washed with acetonitrile and then dried to obtain cross-linked modified nano-calcium carbonate;

[0071] (3) Acidification: 110 g of cross-linked modified nano-calcium carbonate and 4200 g of a 10% hydrochloric acid aqueous solution were mixed, stirred at 300 rpm for 15 min at room temperature, centrifuged at 17000 rpm for 24 min, and the precipitate was taken. The precipitate was washed with deionized water and then dried to obtain acidified microspheres.

[0072] (4) Alkalization: 80 g of acidified microspheres and 4000 g of a 10% sodium hydroxide aqueous solution were mixed, stirred at 300 rpm for 15 min at room temperature, centrifuged at 17000 rpm for 24 min, and the precipitate was taken. The precipitate was washed with deionized water and then dried to obtain nano hollow microspheres;

[0073] 2. Prepare a binder: mix low-density polyethylene resin and inclusion cyclodextrin in a mass ratio of 85:8 to obtain a binder;

[0074] The density of the low-density polyethylene resin is 0.924 g / cm 3 , the melt index at 190°C and 2.16kg is 4.0g / 10min;

[0075] The preparation method of the inclusion cyclodextrin is as follows: 50g of β-cyclodextrin and 3700g of deionized water are mixed, stirred at 40°C at a stirring speed of 300rpm for 20min, 10g of polycaprolactone-polyethylene glycol block copolymer is added, stirring is continued for 20min, naturally cooled to room temperature, ultrasonically vibrated at a frequency of 20kHz for 15min, allowed to stand for 10h, 14g of polyvinyl alcohol is added, stirred at 40°C at a stirring speed of 300rpm for 40min, naturally cooled to room temperature, stirred for 40min, allowed to stand for 10h, spray dried, and the air inlet temperature is controlled at 130°C and the air outlet temperature is controlled at 60°C to obtain the inclusion cyclodextrin;

[0076] The weight average molecular weight of the polycaprolactone-polyethylene glycol block copolymer is 2000, wherein the weight average molecular weight of the caprolactone segment is 1000 and the weight average molecular weight of the ethylene glycol segment is 1000;

[0077] The weight average molecular weight of the polyvinyl alcohol is 10,000, and the alcoholysis degree is 98%;

[0078] 3. Prepare the barrier material: mix the dried ethylene-vinyl alcohol copolymer, high-density polyethylene resin and nano hollow microspheres in a mass ratio of 80:20:7 to obtain the barrier material;

[0079] The preparation method of the dried ethylene-vinyl alcohol copolymer is as follows: drying the ethylene-vinyl alcohol copolymer at 120° C. until the moisture content is 0.01% to obtain the dried ethylene-vinyl alcohol copolymer;

[0080] The molar content of vinyl in the ethylene-vinyl alcohol copolymer is 32%, and the melt index at 210° C. and 2.16 kg is 1.6 g / 10 min;

[0081] The density of the high-density polyethylene resin is 0.961 g / cm 3 , the melt index at 190°C and 2.16kg is 0.7g / 10min;

[0082] The preparation method of the nano hollow microspheres is the same as the preparation method of the nano hollow microspheres in the first step of preparing the polyethylene layer raw material;

[0083] 4. Melt coextrusion: the raw material mixed polyethylene material of polyethylene layer I, the raw material adhesive material of bonding layer I, the raw material barrier material of barrier layer, the raw material adhesive material of bonding layer II, and the raw material mixed polyethylene material of polyethylene layer II are respectively put into five hoppers of the extruder in a mass ratio of 27:16:17:16:27, and melted respectively to obtain melts, and the melts are respectively made to enter different extrusion ports, and extruded in the order of polyethylene layer I, bonding layer I, barrier layer, bonding layer II, and polyethylene layer II, and then introduced into the same die head for composite molding, and then cooled with a chilled roller at 20°C to obtain a cast sheet, and the cast sheet is preheated at 130°C, and then biaxially stretched at 125°C, and the transverse stretching ratio is controlled to be 5:1, and the longitudinal stretching ratio is controlled to be 5:1, and then shaped at 125°C to obtain a five-layer co-extruded polyethylene film;

[0084] The melting temperature of the mixed polyethylene material is 190°C;

[0085] The melting temperature of the bonding material is 185°C;

[0086] The melting temperature of the barrier material is 200°C;

[0087] The average thickness of the five-layer co-extruded polyethylene film is 225 μm.

[0088] This embodiment also provides an application of the five-layer co-extruded polyethylene film obtained by the aforementioned preparation method in a silo bag.

[0089] Example 2

[0090] A method for preparing a five-layer co-extruded polyethylene film, specifically comprising:

[0091] 1. Preparation of mixed polyethylene material: metallocene polyethylene resin, high-density polyethylene resin and nano hollow microspheres are mixed uniformly in a mass ratio of 88:16:6.5 to obtain a mixed polyethylene material;

[0092] The density of the metallocene polyethylene resin is 0.918 g / cm 3 , the melt index at 190°C and 2.16kg is 1.0g / 10min;

[0093] The density of the high-density polyethylene resin is 0.961 g / cm 3 , the melt index at 190°C and 2.16kg is 0.7g / 10min;

[0094] The preparation method of the hollow nanospheres is as follows:

[0095] (1) Surface modification: 95 g of nano-calcium carbonate, 550 g of vinyltrimethoxysilane and 8000 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 150 rpm for 35 min, ammonia water was added dropwise to adjust the pH to 8.5, stirring was continued for 5.5 h, centrifuged at a centrifugal speed of 10000 rpm for 15 min, the precipitate was taken, the precipitate was washed with anhydrous ethanol and then dried to obtain surface-modified nano-calcium carbonate;

[0096] The particle size of the nano calcium carbonate is 100 nm;

[0097] The mass content of the ammonia water is 25%, and the dropping speed is 5g / min;

[0098] (2) Cross-linking modification: 105 g of surface-modified nano-calcium carbonate, 330 g of methacrylic acid, 240 g of divinylbenzene and 33,000 g of acetonitrile were mixed, stirred and refluxed at 95° C. for 15 min, 5 g of azobisisobutyronitrile was added, and the mixture was stirred and refluxed for 2.5 h. The mixture was centrifuged at 10,000 rpm for 15 min, the precipitate was taken, and the precipitate was washed with acetonitrile and then dried to obtain cross-linked modified nano-calcium carbonate;

[0099] (3) Acidification: 115 g of cross-linked modified nano-calcium carbonate and 4300 g of a 10% hydrochloric acid aqueous solution were mixed, stirred at 350 rpm for 18 min at room temperature, centrifuged at 17000 rpm for 25 min, and the precipitate was washed with deionized water and then dried to obtain acidified microspheres;

[0100] (4) Alkalization: 85 g of the acidified microspheres and 4200 g of a 10% sodium hydroxide aqueous solution were mixed, stirred at 350 rpm for 18 min at room temperature, centrifuged at 17000 rpm for 25 min, and the precipitate was washed with deionized water and then dried to obtain nano hollow microspheres;

[0101] 2. Prepare a binder: mix low-density polyethylene resin and inclusion cyclodextrin in a mass ratio of 88:9 to obtain a binder;

[0102] The density of the low-density polyethylene resin is 0.924 g / cm 3 , the melt index at 190°C and 2.16kg is 4.0g / 10min;

[0103] The preparation method of the inclusion cyclodextrin is as follows: 52g of β-cyclodextrin and 3900g of deionized water are mixed, stirred at 45°C at a stirring speed of 350rpm for 25min, 11g of polycaprolactone-polyethylene glycol block copolymer is added, stirring is continued for 25min, naturally cooled to room temperature, ultrasonically vibrated at a frequency of 20kHz for 18min, allowed to stand for 11h, 15g of polyvinyl alcohol is added, stirred at 45°C at a stirring speed of 350rpm for 45min, naturally cooled to room temperature, stirred for 45in, allowed to stand for 11h, spray dried, and the air inlet temperature is controlled to be 135°C and the air outlet temperature is controlled to be 65°C to obtain the inclusion cyclodextrin;

[0104] The weight average molecular weight of the polycaprolactone-polyethylene glycol block copolymer is 2000, wherein the weight average molecular weight of the caprolactone segment is 1000 and the weight average molecular weight of the ethylene glycol segment is 1000;

[0105] The weight average molecular weight of the polyvinyl alcohol is 10,000, and the alcoholysis degree is 98%;

[0106] 3. Prepare the barrier material: mix the dried ethylene-vinyl alcohol copolymer, high-density polyethylene resin and nano hollow microspheres in a mass ratio of 82:21:7.5 to obtain the barrier material;

[0107] The preparation method of the dried ethylene-vinyl alcohol copolymer is as follows: drying the ethylene-vinyl alcohol copolymer at 120° C. until the moisture content is 0.02% to obtain the dried ethylene-vinyl alcohol copolymer;

[0108] The molar content of vinyl in the ethylene-vinyl alcohol copolymer is 32%, and the melt index at 210° C. and 2.16 kg is 1.6 g / 10 min;

[0109] The density of the high-density polyethylene resin is 0.961 g / cm 3 , the melt index at 190°C and 2.16kg is 0.7g / 10min;

[0110] The preparation method of the nano hollow microspheres is the same as the preparation method of the nano hollow microspheres in the first step of preparing the polyethylene layer raw material;

[0111] 4. Melt coextrusion: the raw material mixed polyethylene material of polyethylene layer I, the raw material adhesive material of bonding layer I, the raw material barrier material of barrier layer, the raw material adhesive material of bonding layer II, and the raw material mixed polyethylene material of polyethylene layer II are respectively put into five hoppers of the extruder in a mass ratio of 28:17:19:17:28, and melted respectively to obtain melts, and the melts are respectively made to enter different extrusion ports, and extruded in the order of polyethylene layer I, bonding layer I, barrier layer, bonding layer II, and polyethylene layer II, and then introduced into the same die head for composite molding, and then cooled with a chilled roller at 20°C to obtain a cast sheet, and the cast sheet is preheated at 135°C, and then biaxially stretched at 130°C, and the transverse stretching ratio is controlled to be 5:1, and the longitudinal stretching ratio is controlled to be 5:1, and then shaped at 135°C to obtain a five-layer co-extruded polyethylene film;

[0112] The melting temperature of the mixed polyethylene material is 195°C;

[0113] The melting temperature of the binder is 190°C;

[0114] The melting temperature of the barrier material is 205°C;

[0115] The average thickness of the five-layer co-extruded polyethylene film is 231 μm.

[0116] This embodiment also provides an application of the five-layer co-extruded polyethylene film obtained by the aforementioned preparation method in a silo bag.

[0117] Example 3

[0118] A method for preparing a five-layer co-extruded polyethylene film, specifically comprising:

[0119] 1. Preparation of mixed polyethylene material: metallocene polyethylene resin, high-density polyethylene resin and nano hollow microspheres are uniformly mixed in a mass ratio of 90:18:7 to obtain a mixed polyethylene material;

[0120] The density of the metallocene polyethylene resin is 0.918 g / cm 3 , the melt index at 190°C and 2.16kg is 1.0g / 10min;

[0121] The density of the high-density polyethylene resin is 0.961 g / cm 3 , the melt index at 190°C and 2.16kg is 0.7g / 10min;

[0122] The preparation method of the hollow nanospheres is as follows:

[0123] (1) Surface modification: 100 g of nano-calcium carbonate, 600 g of vinyltrimethoxysilane and 8500 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 200 rpm for 40 min, ammonia water was added dropwise to adjust the pH to 9, stirring was continued for 6 h, centrifuged at a centrifugal speed of 11000 rpm for 16 min, the precipitate was taken, the precipitate was washed with anhydrous ethanol and then dried to obtain surface-modified nano-calcium carbonate;

[0124] The particle size of the nano calcium carbonate is 100 nm;

[0125] The mass content of the ammonia water is 25%, and the dropping speed is 6g / min;

[0126] (2) Cross-linking modification: 110 g of surface-modified nano-calcium carbonate, 360 g of methacrylic acid, 260 g of divinylbenzene and 35,000 g of acetonitrile were mixed, stirred and refluxed at 100° C. for 20 min, 6 g of azobisisobutyronitrile was added, and the mixture was stirred and refluxed for 2.5 h. The mixture was centrifuged at 11,000 rpm for 16 min, and the precipitate was washed with acetonitrile and then dried to obtain cross-linked modified nano-calcium carbonate;

[0127] (3) Acidification: 120 g of cross-linked modified nano-calcium carbonate and 4500 g of a 10% hydrochloric acid aqueous solution were mixed, stirred at 400 rpm for 20 min at room temperature, centrifuged at 18000 rpm for 26 min, and the precipitate was taken, washed with deionized water, and then dried to obtain acidified microspheres;

[0128] (4) Alkalization: 90 g of the acidified microspheres and 4500 g of a 10% sodium hydroxide aqueous solution were mixed, stirred at 400 rpm for 20 min at room temperature, centrifuged at 18000 rpm for 26 min, and the precipitate was taken. The precipitate was washed with deionized water and then dried to obtain nano hollow microspheres;

[0129] 2. Prepare a binder: mix low-density polyethylene resin and inclusion cyclodextrin in a mass ratio of 90:10 to obtain a binder;

[0130] The density of the low-density polyethylene resin is 0.924 g / cm 3 , the melt index at 190°C and 2.16kg is 4.0g / 10min;

[0131] The preparation method of the inclusion cyclodextrin is as follows: 55g of β-cyclodextrin and 4000g of deionized water are mixed, stirred at 50°C and 400rpm for 30min, 12g of polycaprolactone-polyethylene glycol block copolymer is added, stirring is continued for 30min, naturally cooled to room temperature, ultrasonically vibrated at a frequency of 25kHz for 20min, allowed to stand for 12h, 16g of polyvinyl alcohol is added, stirred at 50°C and 400rpm for 50min, naturally cooled to room temperature, stirred for 50min, allowed to stand for 12h, spray dried, and the air inlet temperature is controlled to be 140°C and the air outlet temperature is controlled to be 70°C to obtain the inclusion cyclodextrin;

[0132] The weight average molecular weight of the polycaprolactone-polyethylene glycol block copolymer is 2000, wherein the weight average molecular weight of the caprolactone segment is 1000 and the weight average molecular weight of the ethylene glycol segment is 1000;

[0133] The weight average molecular weight of the polyvinyl alcohol is 10,000, and the alcoholysis degree is 98%;

[0134] 3. Prepare the barrier material: mix the dried ethylene-vinyl alcohol copolymer, high-density polyethylene resin and nano hollow microspheres in a mass ratio of 85:23:8 to obtain the barrier material;

[0135] The preparation method of the dried ethylene-vinyl alcohol copolymer is as follows: drying the ethylene-vinyl alcohol copolymer at 125° C. until the moisture content is 0.04% to obtain the dried ethylene-vinyl alcohol copolymer;

[0136] The molar content of vinyl in the ethylene-vinyl alcohol copolymer is 32%, and the melt index at 210° C. and 2.16 kg is 1.6 g / 10 min;

[0137] The density of the high-density polyethylene resin is 0.961 g / cm 3 , the melt index at 190°C and 2.16kg is 0.7g / 10min;

[0138] The preparation method of the nano hollow microspheres is the same as the preparation method of the nano hollow microspheres in the first step of preparing the polyethylene layer raw material;

[0139] 4. Melt coextrusion: the raw material mixed polyethylene material of polyethylene layer I, the raw material adhesive material of bonding layer I, the raw material barrier material of barrier layer, the raw material adhesive material of bonding layer II, and the raw material mixed polyethylene material of polyethylene layer II are respectively put into five hoppers of the extruder in a mass ratio of 30:18:20:18:30, and melted respectively to obtain melts, and the melts are respectively made to enter different extrusion ports, and extruded in the order of polyethylene layer I, bonding layer I, barrier layer, bonding layer II, and polyethylene layer II, and then introduced into the same die head for composite molding, and then cooled with a chilled roller at 25°C to obtain a cast sheet, and the cast sheet is preheated at 140°C, and then biaxially stretched at 135°C, and the transverse stretching ratio is controlled to be 6:1, and the longitudinal stretching ratio is controlled to be 6:1, and then shaped at 140°C to obtain a five-layer co-extruded polyethylene film;

[0140] The melting temperature of the mixed polyethylene material is 200°C;

[0141] The melting temperature of the binder is 195°C;

[0142] The melting temperature of the barrier material is 210°C;

[0143] The average thickness of the five-layer co-extruded polyethylene film is 234 μm.

[0144] This embodiment also provides an application of the five-layer co-extruded polyethylene film obtained by the aforementioned preparation method in a silo bag.

[0145] Comparative Example 1

[0146] Based on the preparation method of the five-layer co-extruded polyethylene film in Example 1, the addition of nano-microspheres is omitted in the first step of preparing the mixed polyethylene material and the third step of preparing the barrier material.

[0147] Comparative Example 2

[0148] Based on the preparation method of the five-layer co-extruded polyethylene film in Example 1, in the second step of preparing the mixed binder, the addition of the inclusion cyclodextrin is omitted.

[0149] Test Example 1

[0150] The water vapor permeability, oxygen permeability, puncture strength, transverse tensile strength, longitudinal tensile strength, dart drop impact strength (A method), and peel strength of the five-layer co-extruded polyethylene films obtained in Examples 1-3 and Comparative Examples 1-2 were tested. Only one sample was tested during the test, and the five-layer co-extruded polyethylene films were observed to see if there was a delamination problem. The results are shown in Table 1:

[0151] Table 1

[0152]

[0153] Test Example 2

[0154] Ten points were taken from the five-layer co-extruded polyethylene films obtained in Examples 1-3 and Comparative Examples 1-2 for thickness testing, with an interval of 10 cm between each point. The maximum thickness and the minimum thickness were recorded, and then the difference between the maximum thickness and the minimum thickness was calculated. The results are shown in Table 2:

[0155] Table 2

[0156]

[0157] Test Example 3

[0158] The water vapor permeability, oxygen permeability, puncture strength, transverse tensile strength, longitudinal tensile strength, dart drop impact strength, and peel strength of the five-layer co-extruded polyethylene films obtained in Examples 1-3 and Comparative Examples 1-2 were tested. During the test, 10 samples were randomly selected for testing, and then the differences between the maximum and minimum values ​​of the tested water vapor permeability, oxygen permeability, puncture strength, transverse tensile strength, longitudinal tensile strength, dart drop impact strength, and peel strength were calculated. The results are shown in Table 3:

[0159] Table 3

[0160]

[0161] It can be seen from the above results that by adding nano-microspheres in the first step of preparing the mixed polyethylene material and the third step of preparing the barrier material, the barrier properties, puncture resistance, tensile strength and impact strength of the prepared five-layer co-extruded polyethylene film can be improved, and the thickness of the prepared five-layer co-extruded polyethylene film can be ensured to be uniform, and the barrier properties, puncture resistance, tensile strength and impact strength are uniformly distributed;

[0162] By adding inclusion cyclodextrin in the second step of preparing the adhesive, the barrier property, puncture resistance, tensile strength, impact strength and peel strength of the prepared five-layer co-extruded polyethylene film can be improved.

[0163] Unless otherwise specified, all percentages used in the present invention are by mass.

[0164] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a five-layer co-extruded polyethylene film, characterized in that: The method comprises the following steps: preparing a mixed polyethylene material, preparing a bonding material, preparing a barrier material, and melt co-extruding; In the preparation of the mixed polyethylene material, the metallocene polyethylene resin, the high-density polyethylene resin and the nano-microspheres are uniformly mixed to obtain the mixed polyethylene material; The preparation method of the nano-microspheres comprises the following steps: surface modification, cross-linking modification, acidification, and alkalization; The surface modification comprises mixing nano calcium carbonate, vinyl trimethoxysilane and anhydrous ethanol, stirring at room temperature, adjusting the pH to 8-9, continuing stirring, centrifuging, washing the precipitate and drying to obtain surface-modified nano calcium carbonate; The cross-linking modification comprises mixing the surface-modified nano-calcium carbonate, methacrylic acid, divinylbenzene and acetonitrile, stirring and refluxing at 90-100° C., adding azobisisobutyronitrile, continuing to stir and reflux, centrifuging, washing the precipitate and drying it to obtain the cross-linked modified nano-calcium carbonate; The acidification comprises mixing the cross-linked modified nano-calcium carbonate and the hydrochloric acid aqueous solution, stirring at room temperature, centrifuging, washing the precipitate and drying to obtain the acidified microspheres; The alkalization comprises mixing the acidified microspheres and the sodium hydroxide aqueous solution, stirring at room temperature, centrifuging, washing the precipitate and drying to obtain nano-microspheres; In the preparation of the binder, low-density polyethylene resin and inclusion cyclodextrin are uniformly mixed to obtain the binder; The preparation method of the inclusion cyclodextrin is as follows: after mixing β-cyclodextrin and deionized water, stirring at 40-50° C., adding polycaprolactone-polyethylene glycol block copolymer, continuing stirring, cooling, ultrasonically shaking, standing, adding polyvinyl alcohol, stirring at 40-50° C., cooling, continuing stirring, standing, spray drying, and obtaining the inclusion cyclodextrin; The barrier material is prepared by uniformly mixing dried ethylene-vinyl alcohol copolymer, high-density polyethylene resin and nano-microspheres to obtain the barrier material; The method for preparing the nano-microspheres is the same as the method for preparing the nano-microspheres in the raw material for preparing the polyethylene layer; In the melt coextrusion, the raw material mixed polyethylene material of polyethylene layer I, the raw material adhesive material of bonding layer I, the raw material barrier material of barrier layer, the raw material adhesive material of bonding layer II, and the raw material mixed polyethylene material of polyethylene layer II are respectively put into five hoppers of the extruder, and melted respectively to obtain melts, and the melts are respectively entered into different extrusion ports, and extruded in the order of polyethylene layer I, bonding layer I, barrier layer, bonding layer II, and polyethylene layer II, and then introduced into the same die head for composite molding, and then cooled to obtain a cast sheet, and the cast sheet is preheated, bidirectional synchronously stretched, and then shaped to obtain a five-layer co-extruded polyethylene film.

2. The method for preparing a five-layer co-extruded polyethylene film according to claim 1, characterized in that: In the preparation of the mixed polyethylene material, the mass ratio of the metallocene polyethylene resin, the high-density polyethylene resin, and the nano-microspheres is 85-90:15-18:6-7; The density of the metallocene polyethylene resin is 0.918 g / cm 3 , the melt index at 190°C and 2.16kg is 1.0g / 10min; The density of the high-density polyethylene resin is 0.961 g / cm 3 The melt index at 190°C and 2.16 kg is 0.7 g / 10 min.

3. The method for preparing a five-layer co-extruded polyethylene film according to claim 1, characterized in that: In the surface modification, the mass ratio of nano calcium carbonate, vinyl trimethoxy silane and anhydrous ethanol is 90-100:500-600:7500-8500; The particle size of the nano calcium carbonate is 100 nm.

4. The method for preparing a five-layer co-extruded polyethylene film according to claim 1, characterized in that: In the cross-linking modification, the mass ratio of the surface-modified nano-calcium carbonate, methacrylic acid, divinylbenzene, acetonitrile and azobisisobutyronitrile is 100-110:300-360:210-260:30000-35000:4-6.

5. The method for preparing a five-layer co-extruded polyethylene film according to claim 1, characterized in that: In the acidification, the mass ratio of the cross-linked modified nano-calcium carbonate to the hydrochloric acid aqueous solution is 110-120:4200-4500; The mass content of the hydrochloric acid aqueous solution is 10%; In the alkalization, the mass ratio of the acidified microspheres to the sodium hydroxide aqueous solution is 80-90:4000-4500; The mass content of the sodium hydroxide aqueous solution is 10%.

6. The method for preparing a five-layer co-extruded polyethylene film according to claim 1, characterized in that: In the preparation of the binder, the mass ratio of the low-density polyethylene resin to the inclusion cyclodextrin is 85-90:8-10; The density of the low-density polyethylene resin is 0.924 g / cm 3 The melt index at 190°C and 2.16 kg is 4.0 g / 10 min.

7. The method for preparing a five-layer co-extruded polyethylene film according to claim 1, characterized in that: In the preparation of the inclusion cyclodextrin, the mass ratio of β-cyclodextrin, deionized water, polycaprolactone-polyethylene glycol block copolymer, and polyvinyl alcohol is 50-55:3700-4000:10-12:14-16; The weight average molecular weight of the polycaprolactone-polyethylene glycol block copolymer is 2000, wherein the weight average molecular weight of the caprolactone segment is 1000 and the weight average molecular weight of the ethylene glycol segment is 1000; The weight average molecular weight of the polyvinyl alcohol is 10,000, and the alcoholysis degree is 98%; The frequency of the ultrasonic oscillation is 20-25kHz, and the duration is 15-20min.

8. The method for preparing a five-layer co-extruded polyethylene film according to claim 1, characterized in that: In the preparation of the barrier material, the mass ratio of the dried ethylene-vinyl alcohol copolymer, the high-density polyethylene resin, and the nano-microspheres is 80-85:20-23:7-8; The preparation method of the dried ethylene-vinyl alcohol copolymer is as follows: drying the ethylene-vinyl alcohol copolymer at 120-125° C. to a moisture content of 0.01-0.04% to obtain a dried ethylene-vinyl alcohol copolymer; The molar content of vinyl in the ethylene-vinyl alcohol copolymer is 32%, and the melt index at 210° C. and 2.16 kg is 1.6 g / 10 min; The density of the high-density polyethylene resin is 0.961 g / cm 3 The melt index at 190°C and 2.16 kg is 0.7 g / 10 min.

9. The method for preparing a five-layer co-extruded polyethylene film according to claim 1, characterized in that: In the melt coextrusion, the mass ratio of the raw material mixed polyethylene material of the polyethylene layer I, the raw material adhesive material of the bonding layer I, the raw material barrier material of the barrier layer, the raw material adhesive material of the bonding layer II, and the raw material mixed polyethylene material of the polyethylene layer II is 27-30:16-18:17-20:16-18:27-30; The melting temperature of the mixed polyethylene material is 190-200°C; The melting temperature of the adhesive is 185-195°C; The melting temperature of the barrier material is 200-210°C; The cooling temperature is 20-25°C; The preheating temperature is 130-140°C; The temperature of the bidirectional synchronous stretching is 125-135°C, the transverse stretching ratio is 5-6:1, and the longitudinal stretching ratio is 5-6:1; The setting temperature is 125-140°C.

10. Use of a five-layer co-extruded polyethylene film obtained by the preparation method according to any one of claims 1 to 9 in a silo bag.

Citation Information

Patent Citations

  • Method of preparing three-layer co-extrusion pipe fittings from polyolefin master batch

    CN103991246A

  • High-barrier bi-directionally stretched polythene film and preparation method thereof

    CN104589749A